Microstructural, optical and ethanol sensing properties of sprayed Li-doped Mn3O4 thin films. (March 2016) - Amara, M.A.; Larbi, T.; Labidi, A.; Karyaoui, M.; Ouni, B.; Amlouk, M.
Graphical abstract: Highlights: Li doped Mn3 O4 was grown on glass substrate via the low cost effective spray pyrolysis technique. Li doping notably tuned the optical band gap of Mn3 O4 thin film. The incorporation of Li ions was found to provide an enhancement of ethanol sensitivity. Abstract: Lithium-doped manganese oxide thin films have been deposited onto glass substrate by the spray pyrolysis technique. The effect on structural, morphological, optical and ethanol sensitivity properties of the films with different Li concentrations was investigated. The X-ray diffraction (XRD) studies of Li doped Mn3 O4 thin films revealed polycrystalline tetragonal structure with lattice parameters: a = 5.73 Å and c = 9.46 Å. The most intense band at 653.26 cm −1 observed in room temperature Raman spectrum of all films corresponds to the tetragonal crystal structure of Mn3 O4 . Optical band gap energy was found to vary in the range of 2.23–2.82 eV by an increase in Li-doping concentration up to 15%. The resistance based gas sensing measurements showed a clear response already at a low ethanol concentration of 0.1%. The films showed promising ethanol sensing behavior; especially the sample doped with 3% of lithium exhibits the most excellent sensing performance.